2008
DOI: 10.3934/nhm.2008.3.345
|View full text |Cite
|
Sign up to set email alerts
|

On the relationships between topological measures in real-world networks

Abstract: Over the past several years, a number of measures have been introduced to characterize the topology of complex networks. We perform a statistical analysis of real data sets, representing the topology of different realworld networks. First, we show that some measures are either fully related to other topological measures or that they are significantly limited in the range of their possible values. Second, we observe that subsets of measures are highly correlated, indicating redundancy among them. Our study thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 22 publications
2
40
0
1
Order By: Relevance
“…The correlations between topological measures strongly depend on the graph under study [14], and results from these studies differ greatly. Some of them argue that most of the measures are strongly correlated and thus can be redundant, while others argue that these correlations are not strong overall.…”
Section: Related Workmentioning
confidence: 94%
See 2 more Smart Citations
“…The correlations between topological measures strongly depend on the graph under study [14], and results from these studies differ greatly. Some of them argue that most of the measures are strongly correlated and thus can be redundant, while others argue that these correlations are not strong overall.…”
Section: Related Workmentioning
confidence: 94%
“…Jamakovic et al [14] collected data from 20 real-life networks from technological, social, biological and linguistic systems, and calculated the correlation coefficients between 14 topological measures. It was observed that subsets of measures were highly correlated, and Principal Component Analysis (PCA) showed that only three dimensions were enough to retain most of the original variability in the data, capturing more than 99% of the total data set variance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the weighted scheme outperforms the naive one. For the Internet, Jamakovic and Uhlig [16] concluded that the in-degrees of the Internet follow a power law distribution f (x) = ax −γ , x ∈ [0, inf). Under this circumstance, we can conduct a similar derivation and obtain the following results.…”
Section: Mapreduce Cheatsmentioning
confidence: 99%
“…According to Jamakovic and Uhlig [16], in a regulatory network, the in-degrees follow an exponential distribution. Let's assume that x follows an exponential distribution, we have, f (x) = K exp(−Kx), x ∈ [0, inf).…”
Section: Mapreduce Cheatsmentioning
confidence: 99%